1997
DOI: 10.2172/674691
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the HBr-based hydrogen production process as being developed by the SRT Group, Inc. Process study

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government Neither the United Statu Government nor any agency thereof, nor any of their employees. makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or uscfuincss of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 1999, a new method was developed by PowerBall Technologies for producing sodium hydride (NaH) and, by extension, Na using sodium hydroxide (NaOH) and methane (CH 4 ), following reaction in Equation ( 18). A United States Department of Energy (DOE) report found that this method had the potential to reduce the cost of NaH/Na by up to a factor of 10 compared to electrolysis (DiPietro & Skolnik 2000). Hence, the viability of sodiothermic reduction of Al 2 S 3 is predicated on the availability of low-cost Na and low cost of recycling of Na in the process.…”
Section: Thermodynamic Assessment Of Sodiothermic Reduction Of Al 2 Smentioning
confidence: 99%
“…In 1999, a new method was developed by PowerBall Technologies for producing sodium hydride (NaH) and, by extension, Na using sodium hydroxide (NaOH) and methane (CH 4 ), following reaction in Equation ( 18). A United States Department of Energy (DOE) report found that this method had the potential to reduce the cost of NaH/Na by up to a factor of 10 compared to electrolysis (DiPietro & Skolnik 2000). Hence, the viability of sodiothermic reduction of Al 2 S 3 is predicated on the availability of low-cost Na and low cost of recycling of Na in the process.…”
Section: Thermodynamic Assessment Of Sodiothermic Reduction Of Al 2 Smentioning
confidence: 99%
“…An additional advantage of the BrOx cycle is its flexibility because it can either be set to produce CO 2 -free hydrogen by substituting HBr oxidation with HBr electrolysis or be used for methane functionalization and the production of chemicals …”
Section: Introductionmentioning
confidence: 99%